Clothing Hanger Injuries: Pediatric Head and Neck Traumas in the United States, 2002‐2012. (6th December 2013) - Walls, Andrew; Pierce, Matthew; Wang, Hongkun; Harley, Earl H.
Abstract : Objective: To discuss pediatric clothing hanger injuries and review the National Electronic Injury Surveillance System to elucidate frequency and promote increased public awareness among pediatric otolaryngologists. Study Design: Cross‐sectional analysis of a national database. Study Setting: National Electronic Injury Surveillance System Database. Methods: A retrospective review of the National Electronic Injury Surveillance System provided a nationally weighted sampling estimate of 394 pediatric incident reports involving clothing hangers. Each incident report was analyzed for impalement, facial laceration, and contusion injuries to the mouth, face, and head. In addition, hospital disposition and location of the described incident were also obtained. Results: Upon review of the National Electronic Injury Surveillance System, incident rates of pediatric oral impalement (95% confidence interval [CI], 0.10‐0.41), facial laceration (95% CI, 0.22‐0.41), and facial abrasion injuries (95% CI, 0.15‐0.44) frequently involved the metal clothing hanger design. In addition, most of the reported injuries occurred within the home and involved lacerations to the oral cavity. Conclusions: This is the first multiyear, nationally representative study to analyze clothing hanger injuries in the pediatric population. We demonstrate that these injuries occur more frequently than the medical literature currently reports and also elucidate that children are more likely to obtain laceration injuries by metal clothing hangers within the home. Furthermore, we provide a recommendation for standardization of the National Electronic Injury Surveillance System such that product safety analysis may occur and reduce further pediatric incidents.